The 'Inexhaustibility' of Jalaram Bapa: Narrative, Presence and Social Service in the Hindu Diaspora. (31st October 2018) - Wood, Martin
Abstract : Food miracles permeate the historical and contemporary Gujarati Hindu landscape, from the homeland to East Africa and throughout the wider diaspora. However, approaches to food miracles differ from one tradition to the next, and approaches to the divine or the saint can often have a direct impact upon a tradition's ethical approach to wider society. This article considers food miracles as they are more widely understood in the Hindu context, especially in the Hindu diaspora, but with a specific focus on the Jalaram Bapa tradition. By engaging both spiritually and physically in this relationship, food miracles offer a direct and personal experience of Jalaram himself. Furthermore, this presence promotes an ethical framework that draws directly upon the narratives that speak of his life, namely that of seva for all, regardless of social status or religious background.